The Plausibility of Applying Dogme Language Teaching Approach in Iranian EFL Classes from Teachers’ Perspective - Janfeshan, Kamran; Sharhan, Asmaa Nader; Janfeshan, Mohammad Mahdi (Cultural Arts Research and Development, 2023)
Over-dependency on manufactured materials and fixed syllabuses in language classrooms hamper both teachers and students from achieving communicative ability. In the Dogme language teaching approach or unplugged teaching, teachers do not rely on these predetermined procedures and they have the freedom to choose the class activities based on the situation of the classroom. This study was an attempt to investigate Iranian English language teachers’ perspectives on the possibility of the application of the Dogme approach as an unplugged teaching methodology in Iranian high school English classes. 100 Iranian EFL teachers took part in the study. The teachers were given a questionnaire aiming to reveal their opinions about the general principles of the Dogme language teaching approach. Then, a semi-structured oral interview was conducted. The analysis of their responses led to the conclusion that the Dogme approach was generally unknown by many Iranian teachers. Only a few teachers applied this approach in their classes. Therefore, it is suggested that the Dogme approach should be introduced and integrated into mainstream English as a foreign language program in Iranian contexts through workshops and in-service classes.